MODERN METHODS AND TECHNOLOGIES OF PSYCHOLOGICAL INFLUENCE ON HUMANS - Oybek Alisherovich Abdullayev (European Science Publishing, 2024)
The article substantiates the relevance of the study of the psychological impact on a person of external factors associated with the dynamism and transformation of the modern information space. In the modern world, a person is exposed to an increasingly open and implicit (hidden and implicit) psychological impact of the information environment. Special attention is paid to online communications and the types of impact that can be implemented there. The purpose of the article was to study scientific concepts such as: "psychological impact" and "psychological impact", the analysis of which is associated with modern methods of psychological impact on a person in a virtual environment. The theory of research methodology is based on related disciplines that reveal the impact of the digitalization of society on the psychological security of the individual, based on scientific literature. The obtained research results made it possible to identify the negative impact of Internet technologies on the psycho-emotional sphere of a person, to understand the mechanisms of its action and to develop psychological protection in a person, the ability to competently dose the time spent on the Internet, to develop a culture of safe and ethical behavior in the Internet space.
Keywords: psychological impact, psychological violence, cyberbullying, cyber- hate, trolling, cyberstalking, flaming.